Bartholomew of Las Casas and decolonial thinking: debates and clarifications - Mora Rodríguez, Luis Adrián (2020)
Abstract: This article studies the work of Bartolomé de Las Casas and its appropiation by decolonial thinking. The relevance of the references to Las Casas that certain authors of this theorical current claim are discussed. The themes that the Spanish author studies with respect to the American Indians are exposed, and the scope of their interpretation is clarified, based on a philosophical and historical contextualization.